2011
DOI: 10.1002/pd.2715
|View full text |Cite
|
Sign up to set email alerts
|

First trimester maternal serum PAPP‐A and free β‐HCG levels in hyperemesis gravidarum

Abstract: HG is associated with elevated levels of PAPP-A and free β-hCG, and such changes are independent of serum indicators of thyroid and liver function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 25 publications
5
19
0
2
Order By: Relevance
“…It still remains elusive whether such diff erences can be attributed to genetic factors related to ethnicity aff ecting outcomes in women with HG, or whether they could be a result of cultural diff erences aff ecting reporting of symptomology. HG is associated with elevated levels of PAPP-A and free β -hCG, as reported by a recent study in the Turkish population (Derbent et al 2011) and numerous other parameters have been analysed in the literature; among those are allergies suggesting a possible autoimmune component and a restrictive diet (Mullin et al 2012). Helicobacter pylori have also been proposed as a possible aetiological factor for HG but this remains controversial (Karadeniz et al 2006).…”
Section: Discussionmentioning
confidence: 89%
“…It still remains elusive whether such diff erences can be attributed to genetic factors related to ethnicity aff ecting outcomes in women with HG, or whether they could be a result of cultural diff erences aff ecting reporting of symptomology. HG is associated with elevated levels of PAPP-A and free β -hCG, as reported by a recent study in the Turkish population (Derbent et al 2011) and numerous other parameters have been analysed in the literature; among those are allergies suggesting a possible autoimmune component and a restrictive diet (Mullin et al 2012). Helicobacter pylori have also been proposed as a possible aetiological factor for HG but this remains controversial (Karadeniz et al 2006).…”
Section: Discussionmentioning
confidence: 89%
“…One observational study demonstrated that women with HG were more likely to have higher levels of pregnancy-associated plasma protein A (PAPP-A) and free human chorionic gonadotropin (hCG) in the first trimester compared with controls 34. Maternal serum concentrations of hCG peak during the first trimester, when HG symptoms are often at their worst 35.…”
Section: Risk Factors For Hgmentioning
confidence: 99%
“…Similarly, symptoms of HG are often more severe in multiple pregnancies and molar pregnancies, which are conditions associated with excessively high hCG levels. However, conflicting reports exist,34–36 and therefore a causal association between HG and hCG has not been established 36. Infection with Helicobacter pylori may play a role in the development of HG in some women.…”
Section: Risk Factors For Hgmentioning
confidence: 99%
“…Belluomini and colleagues 62 used the RINVR as a combined measure of change in nausea, vomiting and retching between the pre-treatment period (mean of days 1-3) and the post-treatment period (mean of days [5][6][7]. The study found a significant reduction in combined scores for both groups (intervention from 12.64 ± 5.7 to 8.69 ± 5.0; p ≤ 0.001; placebo from 11.47 ± 4.9 to 10.03 ± 4.6; p = 0.019).…”
Section: Rhodes Index Of Nausea Vomiting and Retchingmentioning
confidence: 99%
“…In the last 24 hours, for how long have you felt nauseated or sick at your stomach, Not at all ( 1 ) 1 hour or less ( 2 ) 2-3 hours Median length of stay in days: (1) (1) 8 ( , (2) 8. [5][6][7][8][9], (3) 7 (IQR 6-9), (4) 7 (IQR 4-9); comparator (1) 10 (IQR 7-13), (2)(3)(4)(5)(6)(7)(8)(9)(10)(11), (3) 7 ( , (4) (1) 9. [5][6][7][8][9][10][11][12][13][14][15], (2) 9 (IQR 7-11), (3) 8. [5][6][7][8][9][10][11][12], (4) 7 ( ; comparator (1) 11 , (2) 9 ( , (3) 8 ( , (4) Spontaneous abortion: steroid n = 2 (4%), placebo n = 3 (6%); p = 0.6 l Gestational diabet...…”
Section: Motherisk Puqe-24 Scoring Systemmentioning
confidence: 99%